Advancing climate-resilient health: radiology’s role in mitigating climate-related health risks - Palm, Viktoria; Nischwitz, Emily; Kauczor, Hans-Ulrich; Sedaghat, Sam (Frontiers in Climate, 2025)
Global warming poses significant challenges to healthcare systems, with radiology playing a pivotal role in addressing the health impacts of climate change. Rising global temperatures and worsening air pollution are increasing the prevalence of cardiovascular and pulmonary diseases, necessitating targeted radiological interventions. Extreme heat events elevate the risks of thromboembolic conditions, myocardial infarctions, and strokes, while air pollution exacerbates chronic respiratory diseases like COPD and asthma. Advanced imaging technologies, including photon-counting CT, spectral imaging, and automated analysis tools, are crucial for early detection, timely intervention, and monitoring of these conditions, reducing morbidity and mortality rates. Simultaneously, radiology must adopt sustainable practices to minimize its ecological footprint, as the healthcare sector significantly contributes to global energy consumption. Radiological subspecialties, particularly cardiovascular, pulmonary, and neuroradiology, must expand to meet the growing demand for climate-related care. Innovations in imaging techniques, combined with interdisciplinary collaboration, can enhance diagnostic accuracy and efficiency while reducing resource consumption. These advancements not only strengthen the healthcare system’s resilience but also improve population health outcomes. By integrating preventive strategies, optimizing resources, and advancing technologies, radiology can address the health challenges posed by climate change, contributing to a sustainable healthcare system and fostering Climate Resilient Health.